The electronic document. An analysis from Cuban law in times of pandemic (2021)
This article is based on the idea that the issue of evidence is fundamental for the parties to  a civil or commercial proceeding, taking into account that the success of their claims is determined, fundamentally, by the evidentiary activity deployed through the means of evidence legally provided for focusing our attention on the fixity that the fact of proving offers the document as a means of proof of great relevance, widely addressed in the national procedural system, although its electronic variant has not suffered the same fate. The methods of comparative law, theoretical-legal, exegetical, and synthesis analysis were used, with the aim of analyzing the electronic document as a means of admissible evidence in Cuba in times of pandemic making special reference to its demonstrative force and the importance of this to prove facts or consolidate certainties concerning legal trafficking.